Relationship between the complement system and serum lipid profile in patients with rheumatoid arthritis - Rodríguez-González, Dara; García-González, María; Gómez-Bernal, Fuensanta; Quevedo-Abeledo, Juan C.; González-Rivero, Agustín F.; Jiménez-Sosa, Alejandro; González-López, Elena; Heras-Recuero, Elena; Ocejo-Vinyals, J. Gonzalo; González-Gay, Miguel Á.; Ferraz-Amaro, Iván (Frontiers in Immunology, 2024)
Background. The complement system has been linked to the etiopathogenesis of rheumatoid arthritis (RA). Patients with RA exhibit a dysregulated profile of lipid molecules, which has been attributed to the inflammation present in the disease. In this study, we aimed to evaluate the association between a comprehensive assessment of the complement system and the lipid profile of patients with RA. Methods. 430 patients with RA were recruited. New-generation techniques were employed to conduct functional assays of the three pathways of the complement system. Serum levels of various complement components such as C1q, factor D, properdin, lectin, C1-inhibitor, C2, C4, C4b, C3, C3a, C5, C5a, and C9 were assessed. Furthermore, a complete pattern of lipid molecules was measured including high (HDL), low-density lipoproteins (LDL), and lipoprotein (a). Multivariable linear regression analysis was conducted to investigate the association between the complement system and lipid profile in RA patients. Results. After multivariable analysis, several noteworthy associations emerged between the complement system and lipid molecules. Notably, complement components most strongly linked to the lipid profile were C1q and properdin, representing the upstream classical and alternative pathways, along with C3 from the common cascade. These associations demonstrated significance and positivity concerning total cholesterol, LDL, atherogenic index, apolipoprotein B, and lipoprotein(a), suggesting a connection with an unfavorable lipid profile. Interestingly, complement functional assays of the three pathways and activated products such as C3a and C5a showed no correlation with the lipid pattern. Conclusion. The correlation between the complement system and lipid molecule patterns is pronounced in patients with RA. This relationship is predominantly positive and primarily associated with upstream complement components rather than activated ones.